PWE-033 Role of endoscopy in investigating iron deficiency anaemia. (22nd June 2015) - Mulla, M; Ali, F; Ellis, D; Earland, R; Garsaa, T; Abdullah, N
Abstract : Introduction: Incidence of Iron Deficiency Anaemia (IDA) is 2–5% in adult men and post-menopausal women. Common causes include colonic or gastric malignancy, coeliac disease, and poor dietary intake. British Gastro-intestinal Society (BSG) recommends both upper and lower GI investigations in all post-menopausal women and male patients. We evaluated the compliance with these BSG guidelines in investigating patients with IDA. Method: A comprehensive list of all patients referred as 'IDA' obtained from endoscopy department. All referrals in the time period of one year from April 2013–14' were included. All patients were referred as 'Urgent Suspected Cancer'. Gastroscopy, colonoscopy, flexible sigmoidoscopy and histology reports of all patients were reviewed. Results: A total of 412 patients were included. 58% of patients had both OGD and colonoscopy. 25.4% of patients had OGD only. Out of 412 patients included, 302 had anaemia and 89 were not anaemic. Out of 302 anaemic patients, only 185 had IDA. 21 patients were found to have colorectal cancer (CRC) out of which 18 (85.7%) had anaemia. This was statistically significant, p = 0.001 (CI: 65.7%, 95.2%). Out of 18 patients with CRC and anaemia, 13 (72%) had IDA. This was not statistically significant (p = 0.062). None of patients aged below 50 years had CRC. When we compared patients aged 50 years or less to patients over, there was a significant difference in detecting CRC (p = 0.004). In patients more than 70 years, for every increase in age by 1 year there was a 6.5% increased risk of having colorectal cancer, p = 0.002 (CI: 1.023, 1.108). In 70 patients (16.9%) serum ferritin was not checked before endoscopic investigations. 44 (14.2%) patients did not have duodenal biopsy taken during OGD. Conclusion: More than a third of patients did not have both OGD and colonoscopy as per BSG guidelines. Presence of IDA did not increase the risk of getting CRC. None of patients <50 yrs of age had CRC, perhaps age 70 years might be a better criteria. The guidelines were also not followed with regards to serum ferritin and Duodenal biopsies. Disclosure of interest: None Declared.